Performance Analysis of the Energy Efficient Clustering Models in Wireless Sensor Networks - Vancin, Sercan; Erdem, Ebubekir (Ieee, 2017)
In wireless sensor networks, energy-oriented routing and data aggregation methods are being developed owing to the fact that sensor nodes have limited energy and memory capacity. Cluster-based heterogeneous routing protocols, a popular part of routing technology, have proven effective in topology management, energy consumption, data collection or fusion, reliability, or stability in a distributed sensor network. In this paper, SEED (sleep-wake energy balanced distributed) algorithm was compared with both clustering methods such as, LEACH, mod-LEACH and PEGASIS for homogeneous sensor networks and SEP, DEEC and CEEC for heterogeneous sensor networks in terms of the number of alive nodes in the network and the number of packets sent to the base station (BS) as two different scenarios. Simulation results clearly demonstrate that the SEED algorithm is more robust than the other three methods and increases the network efficiency.
24th IEEE International Conference on Electronics, Circuits and Systems (ICECS) -- DEC 05-08, 2017 -- Batumi, GEORGIA
Keywords: Network Efficiency; Clustering Models; Heterogeneous Sensor Networks